How literacy acquisition changes L1 grammatical knowledge - Gedik, Tan (Yearbook of the German Cognitive Linguistics Association, 2025)
Literacy, the ability to read and write, is a relatively recent cultural invention, however, it has profound effects on cognition, and emerging studies also show that it may influence the mental representations of grammar among native speakers. This contradicts the widely-held assumption that all individuals within an L1 community acquire the same grammar unconsciously. The emerging studies indicate that the availability of a writing system, alongside nonverbal reasoning (i.e., reasoning and problem solving skills), and metalinguistic skills fostered by literacy, contributes significantly to ultimate language attainment. Recent scholarship suggests that illiterate individuals exhibit large individual differences in linguistic knowledge and how well they abstracted various grammatical forms, challenging the notion of uniform grammar that is thought to be achieved successfully across native speakers. This article reports on the state-of-the-art of illiteracy-grammar studies and reevaluates this hypothesis by investigating the impact of literacy on L1 grammar knowledge among illiterate speakers and makes suggestions for future studie
Keywords: illiteracy; linguistic knowledge; ultimate language attainment; individual differences; grammar